2022
DOI: 10.1021/acs.analchem.2c02361
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Size-Independent Three-Dimensional Inertial Focusing in High-Aspect-Ratio Asymmetric Serpentine Microchannels

Abstract: High-throughput three-dimensional (3D) focusing of cells is the key prerequisite for enabling accurate microfluidic cell detection and analysis. In this work, we develop a high-aspectratio asymmetric serpentine (HARAS) microchannel for single-line inertial focusing of particles and cells at the 3D center of the channel. The mechanism of 3D focusing is explored by numerical simulation, and the focusing performances of differently sized particles are characterized experimentally at different flow rates. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Microfluidic devices have been widely used to handle particles (either synthetic or biological) for chemical, biomedical, and environmental applications. Focusing particles into a narrow stream is usually a necessary step in many of these devices such as a flow cytometer and a particle sorter. Both externally imposed (e.g., acoustic, electric, magnetic, etc.) and internally induced (e.g., inertial and elastic lift) forces have been utilized to move particles across streamlines for sheath-free focusing. Among these active and passive particle focusing methods, insulator-based dielectrophoresis (iDEP) has received increasing interest because of its easy and robust operation in electrokinetic microfluidic devices that favor integration and automation for point-of-care technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic devices have been widely used to handle particles (either synthetic or biological) for chemical, biomedical, and environmental applications. Focusing particles into a narrow stream is usually a necessary step in many of these devices such as a flow cytometer and a particle sorter. Both externally imposed (e.g., acoustic, electric, magnetic, etc.) and internally induced (e.g., inertial and elastic lift) forces have been utilized to move particles across streamlines for sheath-free focusing. Among these active and passive particle focusing methods, insulator-based dielectrophoresis (iDEP) has received increasing interest because of its easy and robust operation in electrokinetic microfluidic devices that favor integration and automation for point-of-care technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the curving of the serpentine microchannel, a Dean flow will be formed in the cross-section, which applies a F D on cells to modify their equilibrium positions and accelerate the focusing process. 32 The value of the F D can be estimated as: F D = 3π μU D d (ref. 33) (where μ is the fluid dynamic viscosity; and U D is the average velocity of secondary flow and can be expressed as U D = 1.8 × 10 −4 De 1.63 ).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the curving of the serpentine microchannel, a Dean flow will be formed in the cross-section, which applies a F D on cells to modify their equilibrium positions and accelerate the focusing process. 32 The value of the F D can be estimated as: .63 ). 34 Under competing F L and F D , cells will equilibrate at two vertical positions in the symmetric serpentine microchannel at finite Reynolds numbers.…”
Section: Conceptual Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Ni et al [129] simulated, and experimentally verified, the focussing of particles in an asymmetric serpentine channel with high aspect ratio. The authors observed that the periodic turn of the Dean flow causes the particles to migrate in waves within the channel and promotes the 3D single line focusing of the particles.…”
Section: Curved or Serpentine Channelsmentioning
confidence: 99%